A new shadow-ring device for measuring diffuse solar radiation at the surface - de Oliveira, A. P.; Machado, A. J.; Escobedo, João Francisco [UNESP] (Amer Meteorological Soc, 2002)
A new shadow-ring device for measuring diffuse solar radiation at the surface is presented. In this device the seasonal variation of shadow is followed by moving the detector horizontally. This unique characteristic facilitates its application for long and continuous periods of time. The blocking effect caused by the ring and other related geometric properties are formulated considering the diffuse solar radiation isotropic. The correction factor, shadow size, and ring-detector distance are derived as a function of radius and width of the ring, sun position, and local latitude. The largest blocking occurs during summer, when the ring-detector distance and the shadow width are the smallest, and it is compensated by a smaller blocking effect in the winter period. The performance of the new device is verified comparing daily values of diffuse solar radiation measured simultaneously with a similar device from Kipp & Zonen, Inc. The results show a very good agreement (within 2.5%) between both devices. The new device was also able to reproduce the radiometric properties of the local atmosphere based on 3-yr-long measurements of direct solar radiation using a pyrheliometer. The new device can be applied to estimate daily values of diffuse solar radiation at the surface in the range of 30degreesN-30degreesS with results comparable to other similar apparatuses.